Wafer‐fused 1300 nm VCSELs with an active region based on superlattice. Issue 18 (3rd June 2021) - Blokhin, Sergey; Babichev, Andrey; Gladyshev, Andrey; Karachinsky, Leonid; Novikov, Innokenty; Blokhin, Alexey; Rochas, Stanislav; Denisov, Dmitrii; Voropaev, Kirill; Ionov, Alexander; Ledentsov, Nikolay; Egorov, Anton
Abstract: The 1300 nm range vertical‐cavity surface‐emitting lasers with the active region based on InGaAs/InGaAlAs superlattice are fabricated using molecular‐beam epitaxy and the double wafer‐fusion technique. Lasers with the buried tunnel junction diameter of 5 μm have shown single‐mode CW operation with the output optical power of ∼6 mW at 20°C. Opened eye diagrams are observed up to 10 Gbps.